Non-Self-Similar Dead-Core Rate for the Fast Diffusion Equation with Dependent Coefficient - Liping Zhu; Zhengce Zhang (Abstract and Applied Analysis)
We consider the dead-core problem for the fast diffusion equation with spatially dependent coefficient and show that the temporal dead-core rate is non-self-similar. The proof is based on the standard compactness arguments with the uniqueness of the self-similar solutions and the precise estimates on the single-point final dead-core profile.